PENERAPAN STRATEGI PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII7 SMP NEGERI 14 PEKANBARU TAHUN AJARAN 2012/2013 - Mariani Natalina; Yustini Yusuf; Ermadianti ' (Biogenesis, 2013)
This research is a research which is aimed to improve students scientific behavior and biology studying achievement by implementing guided inqury learning strategy in class VIII7 SMPN 14 Pekanbaru in Academic Year 2012/2013. This research was conducted in October-November 2012. The subject of this research was student of class VIII7 of SMPN 14 Pekanbaru. The number of students was 32 students (15 boys and 17 girls). The Parameter was students scientific behaviour that consist of 7 indicators and students studying achievement consisted of comprehension ability, students passing individually and teachers activities. The average of students behaviour in cycle 1 was 77.78% (moderate) increased in cycle 2 in the average of 86.99% (good). Students comprehension ability in cycle 1 was 77.84% (moderate) increased became 83.21% (moderate). The students passing studying in cycle 1 was 59.38% (pass) increased in cycle 2 became 81.25% (pass). Average of teachers activities in cycle 1 was 90.62% (good) increased in cycle 2 became 100% (very good). From the result of this research it can be concluded that the implementation of guided inquiry can improve the students scientific behaviour and students biology studying achievements in class VIII7 SMPN 14 Pekanbaru in Academic Year 2012/2013.Keywords: Guided Inquiry, Scientific Behaviour, Biology Studying Achiement.